THE RELATIONSHIP OF WORK DURATION TO MENSTRUAL DISORDERS - Nabila Virgin Pramesti Pramesti; Budi Prasetyo; Endyka Erye Frety (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: The group of hand-rolled cigarette factory workers is a work group that is at risk of experiencing menstrual disorders. Excessive working time can cause employees to feel tired. Irregular menstrual cycles are a hormonal imbalance in the reproductive system between the hormones estrogen and progesterone. Objectives: The aim of this research is to investigate the connection between working duration and the menstrual cycle Methods: This study was based on a quantitative approach and used a cross-sectional design. Data were gathered through questionnaires from two groups: one group consisting of 37 cigarette factory workers and another group of 38 non-cigarette factory workers. The data were collected using a purposive sampling technique. In this study, work duration was the independent variable, and menstrual disorders were the dependent variable. A Chi-Square statistical test was performed to examine the relationship between these variables, with a significance level of <ɑ 0.05. Results: The outcomes of the statistical analysis indicated that in the factory worker group, the p-value was 0.000 < ɑ (0.05). The majority of respondents who did not experience menstrual disorders had a long duration of work, with a proportion of 96%, which was higher than those with a medium duration of work. Meanwhile, in the non-factory worker group, the p-value was 0.718 > ɑ (0.05). Most respondents who did not experience menstrual disorders had a light work duration, with a proportion of 86%, which was higher than those who experienced menstrual disorders due to moderate work duration. Conclusions: A significant association exists between work duration and menstrual disorders.